A TRANSPARENT TESTA Transcriptional Module Regulates Endothelium Polarity - Coen, Olivier; Lu, Jing; Xu, Wenjia; Pateyron, Stéphanie; Grain, Damaris; Péchoux, Christine; Lepiniec, Loïc; Magnani, Enrico (Frontiers in Plant Science, 2020)
Seeds have greatly contributed to the successful colonization of land by plants. Compared to spores, seeds carry nutrients, rely less on water for germination, provide a higher degree of protection against biotic and abiotic stresses, and can disperse in different ways. Such advantages are, to a great extent, provided by the seed coat. The evolution of a multi-function seed-coat is inheritably linked to the evolution of tissue polarity, which allows the development of morphologically and functionally distinct domains. Here, we show that the endothelium, the innermost cell layer of the seed coat, displays distinct morphological features along the proximal-distal axis. Furthermore, we identified a TRANSPARENT TESTA transcriptional module that contributes to establishing endothelium polarity and responsiveness to fertilization. Finally, we characterized its downstream gene pathway by whole-genome transcriptional analyses. We speculate that such a regulatory module might have been responsible for the evolution of morphological diversity in seed shape, micropylar pore formation, and cuticle deposition.